FcεRI stimulation promotes the differentiation of histamine receptor 1‐expressing inflammatory macrophages. Issue 4 (18th February 2013) - Novak, N.; Peng, W. M.; Bieber, T.; Akdis, C.
Abstract: Background: Monocyte differentiation into dendritic cells or macrophages and recruitment to peripheral organs in chronic inflammatory diseases are directed by allergen challenge via FcεRI as well as the nature of soluble factors in the microenvironment. High‐affinity receptor for IgE stimulation of effector cells results in the release of histamine, which acts on various histamine receptors (HR) 1‐4, expressed by immune cells. Methods: We examined the effect of FcεRI stimulation of human monocytes on H1R expression and function of differentiating cells. The mRNA levels of H1R, H2R and histidine decarboxylase of differentiating cells were detected by quantitative real‐time PCR. Expression of CD1c, CD11c, CD68 and CD163 was detected by flow cytometry. Amount of histamine, IL‐6 and IL‐12p70 in the cell culture was measured with the help of cytometric bead arrays or ELISA assays. Numbers of H1R‐expressing macrophages were evaluated by immunofluorescence double staining of CD68 and H1R on human skin sections. Results: We demonstrated that FcεRI stimulation promotes the generation of H1R‐expressing macrophage‐like cells with enhanced histamine biosynthesis and H1R‐mediated proinflammatory properties. Supporting our in vitro findings, high numbers of H1R‐expressing CD68 pos macrophages were detected in the dermis of atopic dermatitis (AD) skin lesions. Conclusion: Our observations point to a close histamine‐/HR‐mediated activation of dermal macrophages, leading to modified cell differentiation and responsiveness via H1R, which might contribute to the aggravation of allergic skin inflammation in AD.